Lipid-packing defects are sufficient to modulate membrane insertion and the bound state of α-synuclein - Miah J. Turke; Krishna M. Raghavan; Sofiya Maltseva; Daniel H. S. Kerr; Erin J. Adams; Ka Yee C. Lee (Proceedings of the National Academy of Sciences, 2025)
α-Synuclein is an intrinsically disordered neuronal protein that forms an amphipathic helix when it peripherally binds to lipid membranes. This membrane interaction is integral to the protein’s function but is also associated with its dysfunction. Numerous membrane parameters have been identified to promote α-synuclein binding such as high negative charge and low lipid-packing density, which corresponds to greater lipid-packing defects—increased spacing between lipids conferred through curvature, unsaturation, or small headgroups. Despite α-synuclein’s established preference for negatively charged membranes with packing defects, the specific effects that each parameter has on this interaction remains underexplored. With increasing links between α-synuclein-associated diseases and changes in lipid composition, it has become more important to delineate how changes in membrane parameters affect α-synuclein membrane-interactions. Here, we demonstrate using tryptophan fluorescence spectroscopy that while net negative charge does increase the density of α-synuclein bound to a membrane, lipid-packing defects alone are sufficient for α-synuclein to insert. Not only do our results establish a lipid-packing defect requirement for α-synuclein, but they also reveal a packing defect-dependent shift in the ensemble of binding modes of the protein favoring the insertion of the end of its binding domain—a binding mode which has previously been linked to disease mutants of the protein. Overall, this work establishes the significance of lipid-packing defects in contrast to net negative charge for α-synuclein–membrane binding and proposes a lipid-compositionally dependent shift in α-synuclein’s ensemble of bound conformations, which may be relevant for the protein’s function and dysfunction.